Competitiveness under New Perspectives - Karl Aiginger; Susanne Bärenthaler-Sieber; Johanna Vogel (WWWforEurope, 2013)
This paper aims to redefine the term competitiveness to enhance its usefulness for the evaluation of country performance and for policy conclusions. We attempt to establish a definition that is adequate if economic policy strives for a new growth path that is more dynamic, socially inclusive and ecologically sustainable. We tentatively apply the proposed definition to evaluate the "competitiveness" of EU member states as well as to compare Europe's competitiveness with that of the US, Switzerland, Japan and China, where possible. In the first part of the paper, we examine the evolution of the concept from a focus on "inputs" at the firm level (price or cost competitiveness) to economic structure and capabilities at the country level and finally to "outcome" competitiveness, where outcomes are defined in a broad sense and in the context of the WWWforEurope project. We propose to define competitiveness as the "ability of a country (region, location) to deliver the beyond-GDP goals for its citizens". In the second part of the paper, the performance of the EU-27 countries is assessed along the dimensions described above. We begin with price competitiveness and then proceed to economic structure and countries' capabilities regarding innovation, education, the social system, institutions and environmental ambition. We conclude with outcome competitiveness in terms of economic, social and ecological outcomes. Overall, we compile a database of 68 indicators that describe these different aspects of competitiveness. In the third part of the paper, we investigate empirically the relationship between "outcome" and "input" competitiveness for the EU-27 using panel data analysis for the period from 2000 to 2010. We construct a composite indicator for outcome competitiveness consisting of income, social and ecological pillars, following the beyond-GDP literature. This measure is then econometrically related to composite indicators of the three groups of input indicators: price competitiveness, economic structure, and capabilities. The results of panel regressions suggest that both economic structure and capabilities on aggregate are positively related to our measure of outcome competitiveness, while a negative relationship is found for the wage component of price competitiveness. Among the different dimensions of capabilities, ecological ambition and institutions are positively associated with outcome competitiveness. Overall, we conclude that a narrow focus on the price component of competitiveness neglects other aspects of the concept that are likely to be particularly important for high-income economies like the EU-27.
Keywords: O25; L16; 330; Competitiveness; economic growth path; industrial policy; social capital as growth driver; sustainable growth